SIKAP ORANG TUA TERHADAP PERILAKU PORNOGRAFI ANAKNYA DI SMP NEGERI 30 PEKANBARU - Liyandari, Tari Liyandari; Ayub, Daeng Ayub; Suhil, Said Suhil (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: The purpose of this study was to determine the attitude of Parents Against Pornography Behavior son in SMP 30 Pekanbaru. Inibersifat descriptive study with quantitative approach. The population in this study is the eighth grade students in SMP 30 Pekanbaru. The samples in this study is the random sampling. Instruments used in this study was a questionnaire containing 77 items statements, alternatef answer every item has a statement strongly agree categories were given a score of 5 (five), often given a score of 4 (four), less amenable given a score of 3 (three), disagreed were scored 2 (two), and strongly disagree given a score of 1 (one). Based on the findings of the research, the attitudes of parents towards their children pornography behavior in SMP 30 Pekanbaru based on the cognitive aspects of respondents with a positive attitude toward pornography behavior of 54.59%, 12.95% Neutral attitude and be negativ amounted to 27.37%. Based on the affective aspect of respondents with a positive attitude toward pornography behavior of 80.03%, being neutral at 3.28%, and amounted to 20.04% being negativ. While aspk conative respondents positive attitudes toward pornography behavior of 71.45%, 6.06% are neutral, and be negativ by 26.97% on average mean scores were moderate perindikator this can be seen from the aspect of Cognitive obtain mean score 3 , 33 and up to 10.4 with moderate interpretation, then the affective aspect of the mean sd of 4.01 and 17.07 with a high interpretation, then conative aspect of the mean and sd 3.95 17.21 with moderate interpretation. This means that the attitude of parents towards their children pornography behavior in SMP 30 Pekanbaruinto the medium category.Keywords: attitudes of parents, child pornography behavior.